Spontaneous formation of monocrystalline nanostripes in the molecular beam epitaxy of antimony triselenide - Wojnar, Piotr; Chusnutdinow, Sergej; Kaleta, Anna; Aleszkiewicz, Marta; Kret, Slawomir; Domagala, Jaroslaw Z; Ciepielewski, Pawel; Yatskiv, Roman; Tiagulskyi, Stanislav; Suffczy ski, Jan; Suchocki, Andrzej; Wojtowicz, Tomasz (Nanoscale, 2024)
Self-assembled, highly anisotropic nanostructures are spontaneously formed in the molecular beam epitaxy of antimony triselenide on GaAs substrates. These one-dimensional (1D) nanostripes have all the orientations parallel to the substrate surface and preserve the epitaxial relationship with the substrate. The shape of the nanostripes is directly related to the highly anisotropic stibnite structure of antimony triselenide which consists of 1D ribbons held together by weak van der Waals forces. The fabrication of well-ordered arrays of horizontal nanostripes aligned in directions defined by the orientation of the substrate may contribute significantly to the development of electronic circuits and networks composed of interconnected nanostructures leading to applications in neuromorphic devices, gas sensors and polarization-sensitive photodetectors. Self-assembled, highly anisotropic nanostructures are spontaneously formed in the molecular beam epitaxy of antimony triselenide on GaAs substrates.